Adrenomedullin regulated by miRNA-574-3p protects premature infants with bronchopulmonary dysplasia. Issue 5 (27th May 2020) - Gong, Xiaohui; Qiu, Jiajun; Qiu, Gang; Cai, Cheng
Abstract: Bronchopulmonary dysplasia (BPD) is the most common chronic lung disease (CLD) in premature infants. The present study was designed to elucidate the regulation of miRNA-547-3p on adrenomedullin (ADM) during the pathogenesis of BPD. We used Agilent Human 4x44K Gene Expression Microarrays v2 and miRCURY LNA™ microRNA Array to identify the differently expressed miRNA and its potential target genes, and certified them again by luciferase reporter gene analysis. We only retained target genes that met the following two conditions: first, coexisting in two databases, and second, expressing differences, and then identifying target genes by luciferase reporter gene analysis. Thus, we selected miRNA-574-3p and its target gene ADM for further research. We used real-time q-PCR to determine the expression of miRNA-574-3p and its target gene ADM in premature infants with BPD. We used microarray expression to analyze BPD samples and non-BPD samples and found that there were 516 differently expressed probes between them. The 516 differently expressed probes included 408 up-regulated probes and 108 down-regulated probes. The blood samples of BPD infants were detected by real-time q-PCR and found that the expression of miRNA-574-3p was decreased, while the expression of ADM was significantly increased. Luciferase reporter gene analysis showed that hsa-miR-574-3p can regulate the expression of luciferase with ADM 3′UTR, and decrease it by 61.84%. It has been reported in the literature that ADM can protect the premature infants with BPD. The target gene ADM of miRNA-574-3p may contribute to the prevention and treatment of BPD.